2018
DOI: 10.31234/osf.io/r2xvb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Little race or gender bias in an experiment of initial review of NIH R01 grant proposals

Abstract: Many granting agencies allow reviewers to know the identity of a proposal’s Principal Investigator (PI), which opens the possibility that reviewers discriminate on the basis of PI race and gender. We investigated this experimentally with 48 NIH R01 grant proposals, representing a broad spectrum of NIH-funded science. We modified PI names to create separate White male, White female, Black male, and Black female versions of each proposal, and 412 scientists each submitted initial reviews for three proposals. We … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…This progress toward granting par- ity is likely the result of the conscious efforts of governmental funding agencies to collect the necessary data and conduct formal reviews of their own evaluation processes and possible biases (e.g., through the NSF Authorization Act of 2002) (Hosek et al, 2005). In addition to such observational data showing similar success rates for men and women, recent experimental studies also indicate similar granting rates for identical male and female grant applicants (Forscher et al, 2019). Nevertheless, subtle disparities linger.…”
Section: Grant Successmentioning
confidence: 85%
See 1 more Smart Citation
“…This progress toward granting par- ity is likely the result of the conscious efforts of governmental funding agencies to collect the necessary data and conduct formal reviews of their own evaluation processes and possible biases (e.g., through the NSF Authorization Act of 2002) (Hosek et al, 2005). In addition to such observational data showing similar success rates for men and women, recent experimental studies also indicate similar granting rates for identical male and female grant applicants (Forscher et al, 2019). Nevertheless, subtle disparities linger.…”
Section: Grant Successmentioning
confidence: 85%
“…The operation of gender bias in grants and awards has also received limited experimental study. One recent experimental audit study shows no evidence of gender bias in initial grant reviews at NIH (Forscher et al, 2019). Additionally, a review screening 170 papers identified only one study that directly assessed the effect of gender bias in grant review (Tricco et al, 2017).…”
Section: Publications Grants and Awardsmentioning
confidence: 99%
“…In opposition to the studies indicating that women are consistently undervalued during their application evaluations, a growing literature has in fact argued for the absence of gender differences, asserting that women and men have relatively equal chances to obtain grant funding in different academic disciplines and countries (e.g. Belgian Fonds de la Recherche Scientifique: Beck & Halloin, 2017 ; NIH: Forscher et al, 2019 ; Kalyani et al, 2015 ; Pohlhaus et al, 2011 ; Warner et al, 2017 ; Medical Research Council of Canada: Friesen, 1998 ; Wellcome Trus: Grant et al, 1997 ; Swiss National Science Foundation: Reinhart, 2009 ; National Health and Medical Research Council of Australia: Ward & Donnelly, 1998 ; RAND Corporation, 2005 ). Contrary to many of the aforementioned studies substantiating gender effects in specific grant schemes and contexts, these findings have been obtained from studies examining large-scale data ensuring sufficient effect sizes and generalisability (Jayasinghe et al, 2003 ; Marsh et al, 2008 , 2011 ).…”
Section: The Current State Of Researchmentioning
confidence: 99%
“… In a large US experiment, NIH-grant proposals were rated just as favorably when the supposed principal investigator was a woman as they were when the PI was a man (Forscher, Cox, et al, 2019).…”
Section: Challenges To the Discrimination Explanation For Stem Gendermentioning
confidence: 99%